Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1111/j.1432-1033.1988.tb14211.x
|View full text |Cite
|
Sign up to set email alerts
|

The subcellular location in rat kidney of the peripheral benzodiazepine acceptor

Abstract: In rat kidney high-affinity binding sites for [3H]Ro-5-4864 and [3H]PK-11195 with the properties of the peripheral-type acceptor were found enriched in mitochondrial (M) and light-mitochondrial-lysosomal (L) fractions on differential centrifugation. When the combined M and L fractions were subjected to sucrose density gradient centrifugation, these binding sites were found enriched at a density of 1.155 g/ml coincident with a population of light mitochondria, whereas a population of heavier mitochondria ( Q = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

1990
1990
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 39 publications
1
16
0
2
Order By: Relevance
“…Various groups have suggested that PBBS are localized to mitochondria [17,18], plasma membrane [19,22] or nuclei [5,21,22]. The enrichment of markers for these components was compared to the enrichment of [3H]PK 11195 binding in each of six subcellular fractions (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various groups have suggested that PBBS are localized to mitochondria [17,18], plasma membrane [19,22] or nuclei [5,21,22]. The enrichment of markers for these components was compared to the enrichment of [3H]PK 11195 binding in each of six subcellular fractions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PBBS ligands have been shown to influence mitochondrial respiration in rat kidney [16] and PBBS have been localized to mitochondria in rat kidney [17] and rat adrenal [18]. Binding sites with nearly identical drug binding parameters however, have been localized to human erythrocyte membrane preparations [19] which lack mitochondria and nuclei [20].…”
mentioning
confidence: 99%
“…In the last decade, the involvement of PBRs in neurological conditions was extensively investigated using PBR ligands or PBR overexpressing cells (Gavish et al, 1999;Fischer et al, 2001;Casellas et al, 2002;Papadopoulos et al, 2006b). Accordingly, PBRs were found to be preferentially localised in the outer membrane of mitochondria (O'Beirne and Williams, 1988;Hirsch et al, 1989). Several studies indicated that PBR-mediated changes in mitochondrial function can play a key role during apoptotic events (Tanimoto et al, 1999;Casellas et al, 2002;Chelli et al, 2004;Azarashvili et al, 2005;Li et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Des exp6riences de liaison du PK11195, ligand sp6cifique des PBR, men6es dans la surr6nale, le testicule, le poumon, le rein, le cceur, le muscle squelettique, le foie et le cerveau du rat ont montr6 que les PBR sont localis6s au niveau de la membrane mitochondriale [5,6,14,95,96]. Des 6tudes compl6mentaires r6alis6es dans la surr6nale [5], le rein et le foie [95,96] ainsi que dans la cellule de Leydig [103] ont permis de pr6ciser la localisation des PBR sur la membrane mitochondriale externe.…”
Section: Ci-unclassified
“…Des 6tudes compl6mentaires r6alis6es dans la surr6nale [5], le rein et le foie [95,96] ainsi que dans la cellule de Leydig [103] ont permis de pr6ciser la localisation des PBR sur la membrane mitochondriale externe. Cependant, la pr6sence de PBR sur la membrane mit0chondriale interne a 6galement 6t6 rapport6e dans le poumon du cobaye [92] ce qui sugg~-re que ces r6cepteurs pourraient 8tre localis6s au niveau des sites de contact entre les membranes mitochondria!es internes et externes [103].…”
Section: Ci-unclassified